Study on bioethanol production from oil palm trunk (OPT) SAP by using saccharomyces cerevisiae kyokai no.7 (ATCC 26422) - Nina Farhana, Mohd Jamaludin (2010)
Bioethanol is by far the most important biofuel worldwide. This is mainly a result of the proven and established process technology in addition to the wide range of raw materials suitable for its production. The aim of this study is the screening of parameter of pH (3-7) and agitation speed (110-250 rpm) that are significance to the fermentation process for the production of bioethanol from oil palm trunk (OPT) sap by yeast Saccharomyces cerevisiae Kyokai no.7(ATCC26422). Fermentation design was set up to gain fermentation profile and validation to further obtaining the data for the screening of parameter for the whole fermentations process at several points of times. Data of ethanol, glucose and cell dry weight concentration has been collected and analyzed. ANOVA was performed to determine interacting factor affecting bio-ethanol production after the main effect was estimated by using Design Expert. Fermentation is more valid at sterile condition with 52.56% difference with non-sterile condition. The optimum pH is 6.75 and optimum agitation is 176.56 rpm. The effect of pH was not significant with only 0.88% contribution and the interactions are more significant for agitation speed at 5.12% of contribution with 8.77% of error from expected result. VIII